2020
DOI: 10.1038/s41550-019-0991-9
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of ammonium salts in comet 67P as explanation for the nitrogen depletion in cometary comae

Abstract: Cometary comae are generally depleted in nitrogen. The main carriers for volatile nitrogen in comets are NH3 and HCN. It is known that ammonia readily combines with many acids like e.g. HCN, HNCO, HCOOH, etc. encountered in the interstellar medium as well as in cometary ice to form ammonium salts (NH4 + X -) at low temperatures. Ammonium salts, which can play a significant role in prebiotic chemistry, are hard to detect in space as they are unstable in the gas phase and their infrared signature is often hidden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(119 citation statements)
references
References 45 publications
4
105
0
1
Order By: Relevance
“…-Comets may contain significant amounts of ammonium salts (Mumma et al 2019) that are likely to account for the to-date observed deficiency of nitrogen in comets (Altwegg et al 2020;Geiss 1987;Poch et al 2020;Quirico et al 2016). -The relative abundances of the volatiles in comets exhibit similarities to the ISM and comet 67P/C-G is no exception (Drozdovskaya et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…-Comets may contain significant amounts of ammonium salts (Mumma et al 2019) that are likely to account for the to-date observed deficiency of nitrogen in comets (Altwegg et al 2020;Geiss 1987;Poch et al 2020;Quirico et al 2016). -The relative abundances of the volatiles in comets exhibit similarities to the ISM and comet 67P/C-G is no exception (Drozdovskaya et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The jury is still out on whether highly volatile species are predominantly trapped in CO 2 as opposed to H 2 O in the case of amorphous ices. However, this discussion must be revisited in the context of the recent discovery of abundant ammonium salts in 67P, that suggest the 'missing' N in comets may be hidden in them (Altwegg et al 2020;Poch et al 2020). These semi-volatile salts can form in the interstellar medium at temperatures below 15 K and then remain stable until warmed to much higher temperatures (see later discussion).…”
Section: On the Ice Phase And Formation Temperature Of 67p/c-gmentioning
confidence: 99%
See 3 more Smart Citations